THE DYNAMIC OF THE SOCIO-AFFECTIVE RELATIONS IN A ROMANIAN RURAL HANDBALL SCHOOL TEAM - Oana RUSU; Rita-Margit HRIȘCĂ; Renato-Gabriel PETREA (Cluj University Press, 2022)
Introduction: It is human nature to interact with the other. Interpersonal relationships appear as an invisible connection beyond the spoken words and the informational content of the communication. Starting from the age peculiarities of the students, from their motor possibilities, but also from the personality of each one, taking into account the affinities in the relationship with the others, the teacher can form a group in which to obtain performance with a rural school team. Objectives: 1) identifying the types and meanings of relationships between group members (acceptance, rejection, indifference relationships) and 2) identifying gender influences on the dynamics of relationships between target group members. Methods: The sociometric test was applied on the handball team of the Romanian rural school, 28 students, 14 14 boys and 14 girls), of different ages, between 11 and 14 years old. The average age of the group is 12.89 years, 13 years for boys and 13.64 years for girls. Results: Male subjects received more positive choices than rejections compared to female subjects. 3 subjects (2 boys and a girl) are the most popular. Most members of the group, 14, are in zone B (Liked more than disliked), 8 b and 6f. Another 7 (1b and 6f) are in zone C (Disliked more than liked). None are in zones E (Rejected) and F (Neglected). Conclusions: The first positive elections were aimed at members of the same gender. Male subjects focused their first positive choices more on same-sex subjects, but most girls focused more on male subjects. The rejection options are oriented towards the other gender. There is at the group level an individualized acceptance according to the personality, qualities and sports abilities of each member of the group. Received 2022 May 09; Revised 2022 June 20; Accepted 2022 June 22; Available online 2022 June 30; Available print 2022 August 30. REZUMAT. Dinamica relațiilor socio-afective într-o echipă de handbal de la o școală rurală românească. Introducere. Stă în natura omului să interacționeze cu celălalt. Relațiile interpersonale apar ca o conexiune invizibilă aflată dincolo de cuvintele rostite și de conținutul informațional al comunicării. Plecând de la particularitățile de vârstă ale elevilor, de la posibilitățile motrice ale acestora, dar și de la personalitatea fiecăruia, ținând cont și de afinitățile în relaționarea cu ceilalți, profesorul poate alcătui un grup în care să obțină performanță cu o echipă școlară din mediul rural. Obiective. 1) identificarea tipurilor și sensurilor relațiilor dintre membrii grupului (relații de acceptare, respingere, indiferență) și 2) identificarea influențelor genului asupra dinamicii relațiilor dintre membrii grupului vizat. Metode. Testul sociometric a fost aplicat pe echipa re handbal a școlii din mediul rural românesc, 28 de elevi, 14 14 băieți și 14 fete), de vârste diferite, cuprinse între 11 și 14 ani. Media vârstei grupului este de 12,89 ani, 13 ani pentru băieți, respectiv 13,64 ani pentru fete. Rezultate. Subiecții de gen masculin au primit mai multe alegeri pozitive decât respingeri în comparație cu subiecții de gen feminin. 3 subiecți (2 băieți și o fată) sunt cei mai populari. Cei mai mulți membri ai grupului, 14, sunt în zona B (Liked more than disliked), 8 b și 6f. Alți 7 (1b și 6f) sunt în zona C (Disliked more than liked). Niciunul nu e în zonele E (Rejected) și F (Neglected). Concluzii. Primele alegeri pozitive au fost orientate către membrii de același gen. Subiecții de gen masculin și-au orientat primele alegeri pozitive mai mult către subiecții de același gen, însă cele mai multe fete s-au orientat mai mult către subiecții de gen masculin. Opțiunile de respingeri sunt orientate către genul celălalt.. Există la nivelul grupului o acceptare individualizată în funcție de personalitatea, calitățile și abilitățile sportive ale fiecărui membru al grupului. Cuvinte cheie: relaţie socio-afectivă, handbal, Group Dynamics, personalitate, sociometrie